2021
DOI: 10.1128/jb.00678-20
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory Involvement of the PerR and SloR Metalloregulators in the Streptococcus mutans Oxidative Stress Response

Abstract: Streptococcus mutans is a commensal of the human oral microbiome that can promote dental caries under conditions of dysbiosis. This study investigates metalloregulators and their involvement in the S. mutans oxidative stress response. Oxidative stress in the human mouth can derive from temporal increases in reactive oxygen species (ROS) after meal consumption and from endogenous bacterial ROS-producers that colonize the dentition. We hypothesize that the S. mutans PerR (SMU.593) and SloR (SMU.186) metalloregul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 60 publications
(63 reference statements)
0
10
0
Order By: Relevance
“…Further, the overlap of the motifs for PerR and Rex highlights the control these proteins have on rmlD expression. Canonically, PerR is considered a repressor, while Rex has been shown to act as an activator or repressor of gene expression, dependent on the gene being regulated (30, 32, 33, 35, 37, 38). Our results support these previous findings, where rmlD expression was elevated in the absence of PerR, or when its binding motif was disrupted, upon exposing a culture to H 2 O 2 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, the overlap of the motifs for PerR and Rex highlights the control these proteins have on rmlD expression. Canonically, PerR is considered a repressor, while Rex has been shown to act as an activator or repressor of gene expression, dependent on the gene being regulated (30, 32, 33, 35, 37, 38). Our results support these previous findings, where rmlD expression was elevated in the absence of PerR, or when its binding motif was disrupted, upon exposing a culture to H 2 O 2 .…”
Section: Discussionmentioning
confidence: 99%
“…PerR is a member of the Fur family of transcriptional regulators that regulate iron homeostasis and expression of oxidative stress response genes in streptococci (27)(28)(29)(30). The genes dpr (SMU.540), ahpCF (SMU.764-765), and sod (SMU.629) have all been shown to be negatively regulated, or repressed, by PerR (23,28,31,32). Loss of PerR in S. mutans has been shown to result in decreased susceptibility to hydrogen peroxide (23).…”
Section: Introductionmentioning
confidence: 99%
“…When S. mutans is threatened by H 2 O 2 produced by Streptococcus gordonii or S. sanguinis , SloR can activate the expression of S. mutans oxidative stress adaptation genes (such as dpr and sod ) at an early stage (Crepps et al., 2016). But caseinolytic protease (Clp) proteolytic systems degrade SloR proteins in the H 2 O 2 environment (Ruxin et al, 2021). Therefore, the regulation system of oxidative stress adaptation mechanism of S. mutans is compilated.…”
Section: Regulatory Mechanisms Of Oxidative Stress Adaptation In S Mu...mentioning
confidence: 99%
“…The upregulation of dpr was observed in perR single‐knockout or sloR and perR double‐knockout strains, and further reduced the ROS damage to cells (Brenot et al., 2007; Faulkner & Helmann, 2011; H. J. Wu et al., 2006). Furthermore, studies have shown that when S. mutans is exposed to H 2 O 2 , the perR gene is upregulated, and bind to specific sequences in the sloR operon to inhibit sloR transcription (Ruxin et al, 2021).…”
Section: Regulatory Mechanisms Of Oxidative Stress Adaptation In S Mu...mentioning
confidence: 99%
See 1 more Smart Citation